EFFECTS OF CANVA-BASED MULTIMODAL LEARNING ON WRITING AND VOCABULARY: A QUASI-EXPERIMENTAL STUDY - Elit Nurjannah; Dwita Laksmita Rachmawati (Indonesian EFL Journal, 2026)
The integration of digital technology in English Language Teaching (ELT) has transformed instructional practices toward more interactive and student-centered learning environments. However, previous studies mainly focus on single language skills and often employ descriptive or pre-experimental designs, resulting in limited empirical evidence on integrated language development. This study aims to examine the effectiveness of Canva-based multimodal learning in improving students' vocabulary mastery and writing skills. A quasi-experimental design with a pre-test-post-test control group was employed involving 60 secondary school students divided into experimental and control group. The experimental group received Canva-based multimodal instruction, while the control group was taught using conventional methods. Data were analyzed using Shapiro-Wilk and Lavene's tests, followed by paired and independent sample t-tests, and Cohen's d. The results show a statistically significant improvement in the experimental group compared to the control group (p < 0,05), with a large effect size (d = 0.91). Canva-based multimodal learning effectively enhances both vocabulary mastery and writing skills by promoting deeper cognitive processing through visual and verbal integration.